Experimental study of a single basin solar water still coupled with evacuated glass tubes and external condenser - Hoang , Văn Viết; Tran, Xuân An; Nguyen , Thế Bảo (Journal of Technical Education Science, 2016)
In this research paper, the authors describe the specification and study result of a single basin solar water still coupled with evacuated glass tubes and external condenser. The combination of 8 evacuated glass tubes and an area of 0,84 m2 of external condenser in Single Basin solar water still with an evaporating area of 0,6 m2, the water production of the equipment reached 6 kg/day corresponding to the average radiation 517,54 W/m2 in the weather condition of Ho Chi Minh city.